(untitled) (Bangladesh Journal of Medicine, 2022)
Background: The life expectancy of human is increasing worldwide, and the elderly population represents a large group throughout the world and also in Bangladesh. Globally it is a challenge to overcome elderly comorbidities, and now it is also a challenge that how our elder people can lead a good health and we can use that elderly population as a partner of our socio-economic development. The objectives were to find out the most common comorbidities in elderly population in our society and to give more emphasis for prevention and better management of those comorbid conditions and allow them to lead a healthy living. Methods: This prospective observational study was done in a General Hospital in Faridpur of Bangladesh from October 2019 to December 2020 for a period of one year and three month. Patients of age 60 years and above were selected randomly of all sexes and races. All the information was recorded in fixed protocol. Results: The study was included total 1043 elderly patients, among this male patients were 34.49% and female patients were 65.51%. Most of them presented with single disease in 53.30%. Others presented with two, three and four or more comorbidities (27.99%, 13.32%, and 5.36% respectively). Most common comorbidities were Hypertension (HTN) in 35.37%, Diabetes mellitus (DM) in 28.37%, obstructed airway diseases in 26.84%, Osteoarthritis in 19.94%, Ischemic Heart Diseases (IHD) in 18.88%, Osteoporosis 7.47% and cerebrovascular diseases 4.60%. Conclusion: A large proportion of the population, especially those aged 60, is affected by multicomorbidities. The comorbidities found most of them are preventable. Bangladesh J Medicine 2022; 33: 269-273